Makna Persatuan dalam Berbangsa (Analisis Filosofis Nilai Agama Untuk Persatuan Bangsa): The Meaning of Unity in the Nation (Philosophical Analysis of Religious Values ​​for National Unity) - Sahadewa, Ngurah Weda; Effendhy, Syafiq; Yuliantoro, Mochammad Najib (Jurnal Filsafat Indonesia, 2025)
Religion is a reality that needs to be expressed wisely. Philosophy can play a role in that so that this research is important to be used as one of the thoughts. Religion in religious values ​​is needed for unity. National unity is one of them that is analyzed to make religious values ​​have a special role philosophically. That role is analyzed on the occasion of seeing critically how national unity can be understood. National unity is important to be studied more deeply philosophically so that it can produce a deep understanding related to the meaning of unity. Unity in a nation requires meaning in relation to the existence of religion. Religion has the opportunity to be analyzed philosophically. The analysis is in the form of a philosophical analysis of religious values ​​for national unity. The results of this study are in the form of the fact that religious values ​​for national unity exist in the reality of the truth of understanding. Understanding that awareness to maintain humanity in the existence of a nation. There needs to be interconnectedness with efforts of religious values ​​that can support the welfare of the nation together. A united nation is needed when an agreement has been reached to maintain integrity as a nation. The reality of the unity of the nation can be supported by the existence of religious values ​​that can be empowered philosophically. The ability to unite as a nation is crucial in determining and deciding the future of the nation itself.